2014
DOI: 10.1002/app.40845
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a chitosan‐based flame‐retardant synergist and its application in flame‐retardant polypropylene

Abstract: A novel flame-retardant synergist, chitosan/urea compound based phosphonic acid melamine salt (HUMCS), was synthesized and characterized by Fourier transform infrared spectroscopy and 31 P-NMR. Subsequently, HUMCS was added to a fireretardant polypropylene (PP) compound containing an intumescent flame-retardant (IFR) system to improve its flame-retardant properties. The PP/IFR/HUMCS composites were characterized by limiting oxygen index (LOI) tests, vertical burning tests (UL-94 tests), microscale combustion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Few studies proposed to replace the acid source by bio-based component: more specifically, fumaric acid and phytic acid were proposed as suitable candidates to develop intumescent system with PLA [70]. Bio-based carbonizing agents such as starch [71], cyclodextrin [72] and chitosan [73] have been proposed and showed high efficiency. Among those entirely bio-based carbonizing agents, lignin has also been considered by some researchers due to its abundance in nature and high charring capacity.…”
Section: Fire Retardant Textile Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies proposed to replace the acid source by bio-based component: more specifically, fumaric acid and phytic acid were proposed as suitable candidates to develop intumescent system with PLA [70]. Bio-based carbonizing agents such as starch [71], cyclodextrin [72] and chitosan [73] have been proposed and showed high efficiency. Among those entirely bio-based carbonizing agents, lignin has also been considered by some researchers due to its abundance in nature and high charring capacity.…”
Section: Fire Retardant Textile Applicationsmentioning
confidence: 99%
“…In this context efforts have been extended, especially from the last 10 years, to use different eco-friendly bio-based extracted plant resources and other natural resources due to the desire to promote a "green concept". Thus, the formulation of intumescent flame retardant (IFR) systems may be based on bio-based acidic source such as phytic acid [87], metallic phytates [64], different bio-based carbonization agents like chitosan [73], cyclodextrin [72] and starch [71] exploiting melt blending processes. Among bio-based carbonizing agents, lignin has also been considered as an effective char former due to its highly aromatic structure.…”
Section: Melt Blending and Spinning With Fire Retardant Additivesmentioning
confidence: 99%
“…They provide very robust fire safety and flame resistance performance. The carbon agent forms multicellular charred layers, the char may be soft or hard [5]. Soft char IFRs: composed of a carbon source pentaerythritol (PER), acid source (ammonium polyphosphate) and a gas-blowing additive (melamine) harder char IFRs: composed of sodium silicates and graphite.…”
Section: Intumescent Frsmentioning
confidence: 99%
“…It has been reported that starch [ 24 ], cellulose [ 25 ], and cyclodextrin (CD) [ 26 ] are natural carbon sources, which can be used to replace conventional materials and form new environmentally friendly intumescent flame retardant systems due to the good charring ability. Furthermore, polysaccharides such as alginate and chitosan have been proved to have good retardant properties, which can significantly improve the limiting oxygen index (LOI) of thermal insulation materials [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%